1987
DOI: 10.1152/jappl.1987.63.1.395
|View full text |Cite
|
Sign up to set email alerts
|

Internal carotid and vertebral arterial flow velocity in men at high altitude

Abstract: Cerebral blood flow increases at high altitude, but the mechanism of the increase and its role in adaptation to high altitude are unclear. We hypothesized that the hypoxemia at high altitude would increase cerebral blood flow, which would in turn defend O2 delivery to the brain. Noninvasive Doppler ultrasound was used to measure the flow velocities in the internal carotid and the vertebral arteries in six healthy male subjects. Within 2-4 h of arrival on Pikes Peak (4,300 m), velocities in both arteries were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 0 publications
6
54
2
1
Order By: Relevance
“…During clamp the identical duration and changes in arterial blood gases were replicated while the subjects breathed. 5,260 m. 10,11,27 Conversely, sea level sensitivity to isocapnic or poikilocapnic hypoxia is greater in the VA. 7,12 Euoxic hypocapnia also elicits greater decreases in VA flow through a broad range of PaCO 2 (~15 to 40 mm Hg); 7 however, this is not a universal finding through smaller changes in PCO 2 . 28 It thus seems that during simultaneous changes in PaO 2 and PaCO 2 , ICA and VA reactivities are similar, as was the case in the present study where ICA and VA showed similar profiles during clamp and apnea.…”
Section: Regulation Of Cerebral Blood Flow During Apneamentioning
confidence: 99%
“…During clamp the identical duration and changes in arterial blood gases were replicated while the subjects breathed. 5,260 m. 10,11,27 Conversely, sea level sensitivity to isocapnic or poikilocapnic hypoxia is greater in the VA. 7,12 Euoxic hypocapnia also elicits greater decreases in VA flow through a broad range of PaCO 2 (~15 to 40 mm Hg); 7 however, this is not a universal finding through smaller changes in PCO 2 . 28 It thus seems that during simultaneous changes in PaO 2 and PaCO 2 , ICA and VA reactivities are similar, as was the case in the present study where ICA and VA showed similar profiles during clamp and apnea.…”
Section: Regulation Of Cerebral Blood Flow During Apneamentioning
confidence: 99%
“…Studies of cerebral blood flow (CBF) in humans have found increases of about 20 % over the first 2 days of acclimatization to altitude, with subsequent decreases during the following days (Severinghaus, Chiodi, Eger, Brandstater & Hornbein, 1966;Huang, Moore, McCullough, McCullough, Micco, Fulco, Cymerman, Manco-Johnson, Weil & Reeves, 1987). Understanding these changes is complicated by the fact that the hypoxia and hypocapnia of altitude exposure have opposing effects on CBF.…”
Section: Introductionmentioning
confidence: 99%
“…The general consensus is that upon acute exposure to altitude CBF initially rises and returns to near baseline values within the first few days or 1 -2 weeks of acclimatization (Huang et al, 1987;Jensen et al, 1990;Baumgartner et al, 1994;Lucas et al, 2011;Subudhi et al, 2014). The magnitude in the changes in CBF after altitude exposure depend upon two stimuli with opposing influences on the cerebral circulation: arterial hypoxia and arterial hypocapnia.…”
Section: Discussionmentioning
confidence: 99%
“…The precise pathophysiology of AMS is not known, however, on the basis of early findings increased cerebral blood flow (CBF) in the first few hours of high altitude exposure may play an important role in the pathogenesis of AMS (Huang et al, 1987;Lassen, 1992;Baumgartner et al, 1994). Although early findings indicate that increased CBF is higher in those with AMS than those without AMS symptoms (Baumgartner et al, 1994), this has not been confirmed in later studies (Baumgartner et al, 1999;Dyer et al, 2008;Lucas et al, 2011).…”
Section: Introductionmentioning
confidence: 99%